Child marriage among Somali refugees in Ethiopia: a cross sectional survey of adolescent girls and adult women - Shatha Elnakib; Kara Hunersen; Janna Metzler; Hailu Bekele; W. Courtland Robinson (BMC, 2021)
Abstract Background Despite child marriage receiving increased attention over the past two decades, research on child marriage in humanitarian settings remains scarce. This study sought to quantify child marriage among Somali adolescent girls residing in Kobe refugee camp in Ethiopia and to identify its correlates and consequences. Methods A cross-sectional survey was conducted using multi-stage cluster-based sampling with probability proportional to size. We randomly sampled households that have at least one female aged 15-49 and at least one adolescent female aged 10-19. In addition to calculating the proportion of girls married under age 18, we used survival methods - namely Kaplan Meier graphs and Cox proportional hazard models - to identify risk factors associated with child marriage in this context. We also used descriptive statistics to describe marital age preferences among female adults and presented measures of important sexual and reproductive health indicators among married adolescent girls. Results A total of 603 adult women were surveyed and a household roster was created with information on 3319 household members, of whom 522 were adolescent girls aged 15-19. Of those, 14% were currently married (95% Confidence Interval [CI] 0.11-0.18), and 11% were ever married under age 18 (95% CI 8-15%). Several variables were found to be significantly associated with hazard of child marriage including schooling, sex and employment status of head of household, as well as number of girls under age 18 in the childhood home.. Adult women tended to incorrectly identify minimum legal age at marriage and preferred low marital age for boys and girls - particularly in households of child brides. Among married adolescent girls, contraceptive use was very low (11%; 95% CI 4.94-22.40), and early childbearing was common (60%; 95% CI 45.56-72.89). Conclusions This research contributes to the evidence base on child marriage in humanitarian settings. Insights generated from this study have the potential to inform programs and interventions aiming to prevent and mitigate the impacts of this harmful practice.